Heterogeneity of COVID-19 outbreak in Italy - Rivieccio, Bruno Alessandro; Luconi, Ester; Boracchi, Patrizia; Pariani, Elena; Romanò, Luisa; Salini, Silvia; Castaldi, Silvana; Biganzoli, Elia; Galli, Massimo (Acta Biomedica Atenei Parmensis, 2020)
An outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) started in December 2019 in China and was declared a pandemic on 11.03.2020 by WHO. Italy is one of the most afflicted Country by this epidemic with 136,110 confirmed cases and 16,654 deaths on 9.4.2020 (at the same date, the Ministry of Health was reporting 143,626 cases). During these few months the National Health Service have made a great effort to cope with the increasing request of intensive care beds and all the elective activities in hospital have been suspended. Data from the different Italian regions shows different patterns of positive and dead for this syndrome. Moreover, striking differences of the observed lethality of the infections among different areas were immediately evident from the epidemic reports. It will be of critical relevance to understand the expected evolution of the first lock-down phase, driving the exhaustion of the Covid-19 outbreak.(www.actabiomedica.it)